Italian Validation of the Social Media Engagement Questionnaire (SME-Q): A Preregistered Study - Mirko Duradoni; Federico Innocenti; Alan D. A. Mattiassi; Andrea Guazzini (Human Behavior and Emerging Technologies)
The use of social media has frequently been misunderstood. Scholars worldwide have attempted to investigate patterns in social media use, with several attempts to frame it as a problematic behavior linked to negative consequences. However, among the different attempts, SME-Q has focused on the use per se during critical moments of the day, i.e., around bedtime and during meals. While the use of social media is a behavior adopted by a huge percentage of the population, several differences among countries can be detected that may lead to a different scale dimensionality. As such, in this paper, we translate and validate the Italian version of the SME-Q in order to provide a tool to explore social media use among the Italian population. The study involved 520 people through the compilation of an online survey aimed at investigating psychological and behavioral variables related to social media use which also included three attention checks to control for response biases due to inattention. The study outline, data collection, and analysis plans were preregistered and deposited on the project’s website on the Open Science Framework. The results indicated a novel two-factor structure of the four-item scale with adequate values, revolving around a sleep time factor and a meal factor. The hypothesized relationships with the external validation variables have been confirmed. The successfully validated Italian SME-Q thus allows the exploration of social media engagement with the Italian-speaking population.